2004
DOI: 10.4314/ajst.v4i2.15298
|View full text |Cite
|
Sign up to set email alerts
|

Isotope and geochemical characterization of surface and subsurface waters in the semi-arid Sokoto Basin, Nigeria

Abstract: Stable isotopes and geochemical studies have been applied in the investigation of groundwater resources in Sokoto Basin, northwestern Nigeria. Generally, the characteristic hydrochemical classification in the study area is calcium-alkali-bicarbonate. Surface waters are characterized by alkali-calcium-bicarbonate while groundwater is of Ca-Mg-HCO 3. The plot of δ 18 O versus δ 2 H shows that five isotopic groups can be distinguished. Group I-III is of groundwater origin while group IV and V represent surface wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 2 publications
0
30
0
Order By: Relevance
“…Therefore, groundwater is cheaply found along with low-lying areas and is largely hauled out using handlines from shallow wells particularly in rural areas (Anderson and Ogilbee 1973;Offodile 2002). Groundwater quality studies in Sokoto Basin (du Preez and Berber 1965;Anderson and Ogilbee 1973;Adelana et al 2003;Amadi et al 2015;Ekpoh and Ekpenyong 2011;Ette et al 2017;Toyin et al 2016;, Wali et al 2018a revealed water of excellent quality and of Holocene age (100-10,000 years BP). These studies were carried out in Cretaceous and Cenozoic Sediment sections of north-western and central Sokoto Basin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, groundwater is cheaply found along with low-lying areas and is largely hauled out using handlines from shallow wells particularly in rural areas (Anderson and Ogilbee 1973;Offodile 2002). Groundwater quality studies in Sokoto Basin (du Preez and Berber 1965;Anderson and Ogilbee 1973;Adelana et al 2003;Amadi et al 2015;Ekpoh and Ekpenyong 2011;Ette et al 2017;Toyin et al 2016;, Wali et al 2018a revealed water of excellent quality and of Holocene age (100-10,000 years BP). These studies were carried out in Cretaceous and Cenozoic Sediment sections of north-western and central Sokoto Basin.…”
Section: Introductionmentioning
confidence: 99%
“…However, groundwater has been studied using different techniques: geothermal techniques (Nwankwo 2015;Nwankwo and Shehu 2015;Olatunji and Musa 2013;Toyin et al 2016), isotope techniques (Adelana et al 2003;Geyh and Wirth 1980;Fillion et al 2014Fillion et al , 2018Selck et al 2018;Kattan 2018;Alemayehu et al 2019;Besser et al 2019), multivariate statistics (Mondal et al 2010;Azhar et al 2015;Yidana et al 2018), univariate statistics (Marghade et al 2010;Selvakumar et al 2017;Wali et al 2018a, b), modeling (Ebrahim et al 2019;Locatelli et al 2019), and chemical indices (Marghade et al 2010;Panaskar et al 2016;Wagh et al 2016). Results obtained from these studies showed groundwater quality is influenced by both the natural geogenic processes and anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These water bearing aquifers are either confined or semi confined due to the presence of impervious Clay intercalations which resulted into artesian conditions in some areas in the Basin especially in the Gundumi and Gwandu Formations. [9,17,18,19,20], estimated the water storage, yield and hydraulic properties for the different aquifers in the basin; a yield range of 5,850 to 25,200lph -3 was calculated for the limestone aquifer. Gwandu formation is the most prolific in terms of Groundwater potential in the Sokoto basin, artesian aquifer occurred within this formation.…”
Section: Geology and Hydrogeologymentioning
confidence: 99%
“…Thus, changes in climatic variables/prolong climatic variability in particular rainfall will adversely affect farming operations. Similarly, Adelana et al, (2003) found that infrequent and short period of rainfall (<60 raining days) in most part of the basin prevents the development of agriculture, restricting crop production to only one planting season per year. Given the unique character rainfall Basin, there is need to examine the extent of variability on decadal basis and trend.…”
Section: Introductionmentioning
confidence: 99%